Ex Aequo : mensuel gay d’information/politique, débats, culture. (Paris : Groupe Illico, 1998)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: 99 rue de la Verrerie, 75004 Paris
Frans
Periodiek